THE EFFECTIVENESS OF PROBLEM POSING TYPE OF POST SOLUTION POSING AND COOPERATIVE TYPE OF THINK PAIR SQUARE (TPSQ) LEARNING MODEL FOR STUDENT AT SEVENTH GRADE OF SMP MUHAMMADIYAH 1 SLEMAN IN EVEN SEMESTER OF ACADEMIC YEAR 2015/2016 - Mega Yanalisa Pradina; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
This research is done because of the application of usual teaching system that is dominated by teacher and the learning teaching process is not enjoyable, so that it needs the teaching method involving the students in order the students will be more active and consider learning is enjoyable. This research is purposed to know the effectiveness of Problem Posing type Post Solution Posing and cooperative type of Think Pair Square (TPSQ) learning model for students at seventh grade in SMP Muhammadiyah 1 Sleman in even semester of academic year 2015/2016. The kind of this research is experimental research. The population in this research is the students at seventh grade in SMP Muhammadiyah 1 Sleman of academic year 2015/2016, which is divided into three classes in total ninety six students. Sample taking used random sampling technique so it can be got in class VII C as the experimental class I (Post Solution Posing) and class VII A as the experimental class II (Think Pair Square (TPSQ)). The collecting data is done using documentation and test methods. The analysis data technique used is to pre-requirement analysis test including normality test using Chi-Square formula, homogeneity test using Barlett test formula, and Hypotheses test using t-test. The research’s result in significant level of 5% and db = 62 shows that: (1) there is a difference between the result in learning mathematics in students learning mathematics using Problem Posing type of Post Solution Posing learning model to the students using cooperative type of TPSQ. It is shown in the result of first hypotheses test, it results value = 2,581 > = 1,99962. (2) Problem Posing type of Post Solution Posing is more effective compared by cooperative type of TPSQ. This is seen using the result of second hypotheses test, it results value = 2,581 > = 1,67017.